Chronic stress induces persistent changes in global DNA methylation and gene expression in the medial prefrontal cortex, orbitofrontal cortex, and hippocampus. (13th May 2016) - Mychasiuk, R.; Muhammad, A.; Kolb, B.
Highlights: Chronic stress is associated with sex-dependent functional impairment of the prefrontal cortex and hippocampus. An mRNA sequencing platform identified changes in gene expression for male and female rats exposed to chronic stress. The most pronounced change in gene expression was identified in the OFC (females: 40 genes, males: 17 genes). Pathway analysis software demonstrated contrasting activation of functional networks between the OFC and the mPFC. The ingenuity software also identified sex-dependent activation and regulation of signaling pathways in response to stress. Abstract: Chronic stress is associated with a plethora of cognitive symptoms such as emotional dysregulation and impaired executive function that have been attributed to modifications in neuroanatomy in the orbitofrontal cortex (OFC), medial prefrontal cortex (mPFC), and hippocampus (HPC). While many studies have examined stress-induced changes in neuronal morphology, synaptic plasticity, and cellular function, there has been little investigation into persistent changes in gene expression that may be responsible for the maintenance of these changes. This study exposed adult rats to a chronic stressor and then examined changes in mRNA gene expression in the OFC, mPFC and HPC following a two-week withdrawal period. mRNA bio-sequencing results revealed sex- and region-dependent changes. Surprisingly the greatest changes in gene expression were found in the OFC, and similar to anatomical studies, analysis of gene changes with Ingenuity Pathway Analysis software demonstrated that the mPFC and OFC exhibited contrasting activation of canonical pathways and functional networks. The HPC demonstrated the largest degree of sex-dependent change in gene expression. In general, chronic stress induced persistent changes in gene expression in the three brain regions we examined and these changes could be associated with the commonly reported cognitive symptoms. The current study highlights the region- and sex-dependent nature of the brain's response to chronic stress and the difficulty we face when attempting to develop treatment options.